IMPLEMENTASI SUPPLY CHAIN MANAGEMENT PADA UMKM TENUN TROSO JEPARA - Noor Azizah; Virliana Dicky Pramandari (Computer Society of Nahdlatul Ulama (CSNU) Indonesia, 2018)
The troso weaving produced by SMEs in Jepara currently has a greatly increased public demand, and this has resulted in an increase in the number of suppliers and distributors owned by the troso weaving companies. The company needs to select suppliers so that the received raw materials have quality and price in accordance with the budgeted by the company as well as selecting distributors so that ready-made troso weave is marketed accordingly. To improve the performance of the company, the need for supply chain management (SCM) strategy by taking into account the flow of communication between partners, the ability of the company to establish relationships with suppliers and distributors. System development method used is to use waterfall method which starts from system requirement analysis, system design, implementation, testing, and maintenance. The result of this research is the SCM information system at UMKM Tenoon web-based troso. The benefits of this research are to help SMEs to facilitate in determining the best suppliers and distributors.Keywords: supply chain management, SMEs, troso